Audiovisual resources in the Data Web: The construction of the Semantic Audiovisual Portal - Coneglian, Caio Saraiva [UNESP]; Simionato Arakaki, Ana Carolina; Ventura Amorim Goncalez, Paula Regina; Santarem Segundo, Jose Eduardo [UNESP] (Pontificia Universidade Catolica Campinas, 2019)
In film production, a variety of filmic data is created in all stages of production of the audiovisual resource. These data are valuable for the improvement of databases and later retrieval of information. General information about movies can be found, for example, on Wikipedia and more specifically on the Internet Movie Database. Nonetheless, searches can be more semantic using the Linked Movie Database and DBpedia, but they still need to have understood of the Semantic Web technologies. For this reason, it aims to present the development of the Semantic Audiovisual Portal, which dynamically gathers information from several databases of Linked Data, allowing users to have access to the information that expresses the data relationships and the data meaning. In order to achieve the objectives, the research had as methodological procedures two stages, the first step was a bibliographic survey on the subject, and the second stage, the Semantic Audiovisual Portal was developed, using the o Linked Movie Database, DBpedia, Internet Movie Database and Wikipedia. The results evidenced the semantic potential of the bases listed, as well as the improvement of the SPARQL Protocol and RDF Query Language. It considers that the creation of the architecture and the development of the Semantic. Audiovisual Portal is favored by the use of Semantic Web technologies and Linked Data databases, promoting the materialization of the Semantic Web, at the same time contributing to the audiovisual domain.
Keywords: Movies; Linked data; Audiovisual resources; SPARQL; Semantic Web